2015
DOI: 10.5812/traumamon.21891
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Caregiver Spouses of Veterans With Bilateral Lower Extremity Amputations

Abstract: Background:Providing care for patients with chronic disability affects caregivers’ social lives and relationships and can lead to poor health and lower quality of life.Objectives:In this study, our goal was to assess the quality of life in spouses of war veterans with bilateral lower limb amputations to find factors affecting caregivers’ quality of life.Patients and Methods:In a cross-sectional study, spouses of 244 veterans with war-related bilateral lower limb amputations for at least one year were invited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Some studies reported that the education level of caregivers could influence their HRQoL (Alshubaili et al, 2008 ; Moradi et al, 2015 ; Ndikuno et al, 2016 ). The present study confirmed that FCs of patients with GD with a higher level of education had better physical component scores than those with lower education levels.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that the education level of caregivers could influence their HRQoL (Alshubaili et al, 2008 ; Moradi et al, 2015 ; Ndikuno et al, 2016 ). The present study confirmed that FCs of patients with GD with a higher level of education had better physical component scores than those with lower education levels.…”
Section: Discussionmentioning
confidence: 99%
“…In these women, because of the sensibility of their husband in social relations, disorder, and limited social interactions have been observed (Vagharseyyedin, 2015). Care of chronic patient cause's impaired social relationships and feelings of loneliness, depression, and life dysfunction (Moradi et al, 2015). A qualitative study on veterans' wives stress disorder after the accident t in Iran showed the negative impact on family structure and function are particularly spouses of veterans.…”
Section: Discussionmentioning
confidence: 99%
“…Lower extremity amputation causes physical, psychological, and emotional dysfunction, necessitating caregiver's support for rehabilitation and general health care . Several previous studies have associated amputation care with psychological and financial burden and physical and mental stress on the family; moreover, amputation care has an impact on social relationships.…”
Section: Introductionmentioning
confidence: 99%